TRANSYLVNIA IN SAAVEDRA FAJARDO'S POLITICO-IDEOLOGICAL HORIZON - Monostori, Tibor (Res Publica. Revista de Historia de las Ideas Políticas, 2009)
In this article, the author tracks Saavedra Fajardo’s diplomatic activity within the Thirty Years’ War context together with his positions regarding the relationships of various European States with Protestant Powers or the Ottoman Empire.
Keywords: Saavedra Fajardo; Rákóczi; Transylvania; diplomacy; Ottoman Empire; France; Habsburg; 17th century